Biofilm structures (EPS and bacterial communities) in drinking water distribution systems are conditioned by hydraulics and influence discolouration - Fish, K.; Osborn, A.M.; Boxall, J.B. (The Science of the total environment, 2017)
High-quality drinking water from treatment works is degraded during transport to customer taps through the Drinking Water Distribution System (DWDS). Interactions occurring at the pipe wall-water interface are central to this degradation and are often dominated by complex microbial biofilms that are not well understood. This study uses novel application of confocal microscopy techniques to quantify the composition of extracellular polymeric substances (EPS) and cells of DWDS biofilms together with concurrent evaluation of the bacterial community. An internationally unique, full-scale, experimental DWDS facility was used to investigate the impact of three different hydraulic patterns upon biofilms and subsequently assess their response to increases in shear stress, linking biofilms to water quality impacts such as discolouration. Greater flow variation during growth was associated with increased cell quantity but was inversely related to EPS-to-cell volume ratios and bacterial diversity. Discolouration was caused and EPS was mobilised during flushing of all conditions. Ultimately, biofilms developed under low-varied flow conditions had lowest amounts of biomass, the greatest EPS volumes per cell and the lowest discolouration response. This research shows that the interactions between hydraulics and biofilm physical and community structures are complex but critical to managing biofilms within ageing DWDS infrastructure to limit water quality degradation and protect public health. [Display omitted] •Analysis of drinking water biofilm physical structure and bacterial communities•Biofilms developed naturally in full-scale drinking water distribution facility.•Hydraulic conditions influence cohesive strength of EPS.•Biofilm structure differs between Varied Flow and Steady State conditioned biofilms.•Understanding biofilms, including EPS, is key to safeguarding water quality.